Rapid prototyping a school-based health program in the developing world. (2017) - Levine, David I.; Riggs, William; Steffen, Kelsey
Abstract: Basic sanitation and hygiene can prevent roughly a million deaths a year. This study examines the rapid prototyping of a pilot school-based handwashing, safe water, and sanitation program in Chennai, India. Our content analysis identified challenges in the classroom (Localization; Curriculum supplies; Program implementation; Communication and language; and Teacher commitment), factors outside the class but within the school (School administration and support and Hygiene and sanitation facilities and supplies) and factors outside the school such as family and slum conditions. We report on the pilot, the barriers it faced, and the changes we made in pursuit of a sustainable school-based health program.